Life history impacts on infancy and the evolution of human social cognition - Hawkes, Kristen (Frontiers in Psychology, 2023)
Greater longevity, slower maturation and shorter birth intervals are key life history features that distinguish humans from the other living members of our hominid family, the great apes. My goal here is to synthesize theory and evidence that those features may explain the evolution of both our bigger brains and our cooperative sociality. I rely on Sarah Hrdy’s hypothesis that survival challenges during infancy propelled the evolution of distinctly human socioemotional appetites and Barbara Finlay and colleagues’ findings that mammalian brain size and composition are determined by developmental duration. Similar responsiveness to varying developmental contexts in chimpanzee and human one-year-olds suggests similar infant responsiveness in our nearest common ancestor. Those ancestral infants likely also began to acquire solid food while still nursing, and fed themselves at weaning as chimpanzees and other great apes do now. When human ancestors colonized habitats that lacked foods infants could handle, dependents’ survival became contingent on subsidies. Competition to engage subsidizers selected for capacities and tendencies to enlist and maintain social connections during the early wiring of expanding infant brains with lifelong consequences that Hrdy labeled “emotionally modern” social cognition